EVALUATION OF THE PHYSICAL, PHYTOCHEMICAL, AND HEDONIC QUALITY OF HERBAL POWDERED BEVERAGES COMBINING ELEPHANT GINGER (Zingiber officinale Roscoe), GARLIC (Allium sativum L.), AND CITRONELLA (Cymbopogon nardus L. Rendle) - Atikah, Nur; Ramayani, Septiana Laksmi; Pratiwi, Melinda Eka (Jurnal Jamu Kusuma, 2024)
Hypertension can be managed using traditional medicinal plants such as elephant ginger, garlic, and citronella, which can be processed into instant powdered beverage formulations. This study evaluates the physical quality, phytochemical properties, and hedonic characteristics of powdered formulations combining these three ingredients. The study employed an observational method. Instant powdered formulations were prepared using the crystallization method, with three variations of white sugar to palm sugar ratios: 2:0 (F1), 1.5:0.5 (F2), and 1:1 (F3). A univariate analysis was conducted to evaluate the physical qualities of the powders, including organoleptic properties, pH, moisture content, tapping density, angle of repose, and dissolution time, as well as to report the results of phytochemical screening and hedonic evaluation (taste, aroma, and color). The results revealed variations in the physical properties of the three formulations. The pH values were 5.91, 5.90, and 5.74 for F1, F2, and F3, respectively. Moisture content was recorded at 1%, 1.33%, and 3.33%, while tapping density was 8.33%, 11%, and 11.33%. Flow times were 10.57 seconds, 10.68 seconds, and 11.34 seconds, while the angles of repose were measured at 32.37°, 26.47°, and 37.81°. Dissolution times were recorded as 15.3 seconds, 17.17 seconds, and 18.15 seconds. Formula 1 (F1) demonstrated the best physical quality based on established standards among the formulations. Phytochemical screening for all three formulations (F1–F3) indicated the presence of flavonoids and saponins, while tests for alkaloids and terpenoids yielded negative results. The hedonic evaluation, conducted using F1 due to its superior physical quality, showed that out of 31 respondents, 17 rated it as "like," 8 as "neutral," and 6 as "very like." In conclusion, although the flow time parameter did not meet the standard requirement, F1 exhibited the best physical quality, contained beneficial phytochemicals (flavonoids and saponins), and was well-received by the majority of respondents in terms of taste, aroma, and color.